Development of Burkholderia mallei and pseudomallei vaccines - Silva, Ediane B.; Dow, Steven (Frontiers in Cellular and Infection Microbiology, 2013)
B. mallei and B. pseudomallei are Gram-negative bacteria that cause glanders and melioidosis, respectively. Inhalational infection with either organism can result in severe and rapidly fatal pneumonia. Inoculation by the oral and cutaneous routes can also produce infection. chronic infection develops after recovery from acute infection with both agents, and control of infection with antibiotics requires prolonged treatment. Symptoms for both meliodosis and glanders are non-specific, making diagnosis difficult. B. pseudomallei can be located in the environment, but in the host, B. mallei and B. psedomallei are intracellular organisms. Thefection results in similar immune responses to both agents. Effective early innate immune responses are critical to controlling the early phase of the infection. Innate immune signaling molecules such as TLR, NOD, MyD88 and pro-inflammatory cytokines such as IFN- and TNF-α play key roles in regulating control of infection. Neutrophils and monocytes are critical cells in the early infection for these microorganisms. Both monocytes and macrophages are necessary for limiting dissemination of B. pseudomallei. In contrast, the role of adaptive immune responses in controlling Burkholderia infection is less well understood. However, T cell responses are critical for vaccine protection from Burkholderia infection. At present, effective vaccines for prevention of glanders or meliodosis have not been developed, although recently progress of Burkholderia vaccines has received renewed attention. This review will summarize current and past approaches to develop Burkholderia mallei and pseudomalllei vaccines, with emphasis on immune mechanisms of protection and the challenges facing the field. At present, immunization with live attenuated bacteria provides the most effective and durable immunity, and it is important therefore to understand the immune correlates of protection induced by live attenuated vaccines.